PENINGKATAN PENGETAHUAN REMAJA TENTANG MANFAAT JAHE MERAH TERHADAP PENURUNAN - Suparmi, S. (P3M STIKES Aisyiyah Surakarta, 2017)
The incidence of dysmenorrhea in Indonesia is quite high especially in school children 54.89% Herbal products are currently becoming the main alternative for young women who want to reduce the pain in dysmenorrhea without side effects. Target and the resulting Output is Increased knowledge teenagers about the benefits of ginger against decreased disminore. The method used in the partner group, namely by counseling. Achieved Results: There is an increase in adolescent knowledge that includes knowledge about menstruation, disminore and red ginger benefits. Teenagers know that the content of calcium and vitamin C in red ginger is useful to soothe the nerves and reduce the pain and components of red ginger such as gingerol, shogaol and zingerone give pharmacological and physiological effects such as antioxidants, anti-inflammatory, analgesic, anticarcinogenic, non-toxic and non-mutagenic albeit at high concentrations. Conclusion: Provision of information about the benefits of red ginger to decrease disminore is needed for adolescents who experience disminore.